Analysis Of Factors Influencing Dividend Policy (Study of Pharmaceutical Companies Listed on Idx In 2017-2022) - Alfajri, Yusuf Lutfi; Purwanti, Lilik (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
This study aims to test and analyze factors affecting dividend policy using financial ratios with signaling theory approach. The population of this study includes 11 pharmaceutical companies listed on Indonesia Stock Exchange (IDX), from which 36 samples are selected through purposive sampling. The results of the hypothesis testing by multiple regression analysis exhibit that return on asset (ROA) has a positive effect on dividend policy; total asset turnover (TATO), debt to equity ratio (DER), and firm size have a negative effect on dividend policy; and current ratio (CR) and return on equity (ROE) have no effect on dividend policy.